Penurunan Jumlah Cacat Dan Biaya Bahan Baku Dengan Metode Responsesponsse Surface - Muhammad Lukman; Ahmad Zubaid Firdaus; Rahadian Galih (Jurnal Teknik Industri, 2013)
CV.   Indah Cemerlang  is a  company  for building material which  produces paving  stone. The company  often  changes  the raw materials composition which is affected  by  cost  of raw materials. Change of  the raw  materials composition  makes  product quality  lower. Therefore, a study should be conducted in order to identify  control factors  influencing on defect responsse by using Responsse  Surface  method. Responsse surface method used in this research consists of two stages. First stage, called orde 1, is dealing with screening and second stage, called orde 2, is dealing with optimization. The result of orde 1 shows that the raw materials composition influencing on defect responsse are cement volume and gray stone. According to the result of second stage, the experiment is conducted to determine optimal amount of raw materials composition. Optimal amount of the raw materials composition are 20 liters of water, 47 kilograms of cement, 120 kilograms of sand, and 10.45 doses of gray stone, with value of defect responsse 5.08%. Applying proposed composition can decrease cost of raw material by Rp 49,33 per pallet and cost of poor quality by 47.60 per week.